Evaluation of Golden Proportion Between Maxillary Anterior Teeth (Medical Forum Monthly, 2024)
Objective: The study has been made to scrutinize the occurrence of Golden proportion between maxillary anterior teeth in a group of Pakistani population.Study Design: Cross sectional studyPlace and Duration of the Study: This study was conducted at the Oral Biology Department at Dr. Ishrat ul Ebad Khan Institute of Oral Health Science Dow University for a period of 6 months from August 2014 to January 2015.Materials and Methods: This study comprised 500 volunteers of satisfactory aesthetics, out of which 394 were females and 105 were males between 21 to 30 years of age.First the impression of the subjects was taken with Alginate and cast was made with hard plaster. This was followed by measuring the width of maxillary anterior teeth of both quadrants at the mesio-distal contact point using a Digital caliper. Next, the Golden proportion for all subjects was calculated by multiplying the width of the larger factor by 62% and compared with the width of the smaller factor for proportion to be evaluated.Results: The data highlighted the statistical significant result in the ratio of Golden proportions depending upon gender. 11.2% of the samples have the width of their central incisors in golden proportion to the width of their lateral incisors.9.6% of the subjects had the width of their lateral incisors in golden proportion to the width of their canines. Age showed no significant difference.Conclusion: It is not always correct to assert that golden proportion exists between widths of maxillary anterior teeth in a subject of Pakistani population.